The implantation prospects of integrated reporting for enterprises in Ukraine - Sokil, Oleh; Сокіл, Олег Григорійович; Сокол, Олег Григорьевич; Ortina, Hanna; Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович (My University, 2019)
EN: Problem statement. The purpose of the article is to analyze and evaluate the prospects for the development of in-tegrated reporting for Ukrainian enterprises. Research results. Today, enterprises begin to communicate less exclusively in the language of finance and busi-ness accounting. Entrepreneurship should be focused on behalf of a wider range of stakeholders, and transparency is a good practice. When comparing the Guidelines for the preparation of a management report prepared by GRI and the recommendations of international integrated reporting standards, we can conclude that the requirements for the main sections of the reports are identical. Countries of the world in which official regulation took place much earlier and the process of forming the rules and conditions for the preparation and publication of integrated reports was completed now have the corresponding result of the dissemination of the trend and the need for the pub-lication of integrated reports. Conclusions. Enterprises that are ready to move to a new level of quality of their reporting should review their accounting policies, which should be based on the transition from traditional business accounting to sustainable development accounting. The prospect of implementing integrated reporting is no longer on the agenda. This is a reality that not only acts, but also spreads exponentially. Now for 2019, compulsory reporting is intended only for large and medium-sized enterprises. Their number is 16653 enterprises. But, small enterprises with an appropriate estimate of the book value of assets from 350 thousand to 4 million Euros and net income from sales from 700 thou-sand to 8 million Euros in the near future will be obliged to form and publish reports on their sustainable develop-ment. UK: У статті проаналізовано ставлення та готовність підприємств до формування інтегрованих звітів. Проведено порівняння Методичних рекомендацій зі складання звіту про управління підготовлених МФУ та міжнародних стандартів інтегрованої звітності. Визначена кількість підприємств що формують інтегровану звітність у світі на 2019 рік за стандартом GRI G4 та G3. Доведена потреба трансформації звітності про сталий розвиток під тиском міжнародного і українського нормативно-правового регулювання. Оцінені перспективи впровадження інтегрованої звітності в Україні серед великих, середніх, малих та мікропідприємств.
Перспективи впровадження інтегрованої звітності для підприємств України
Keywords: integrated reporting; accounting; sustainable development; enterprise; інтегрована звітність; облік; сталий розвиток; підприємство